Islamic Legal Approach to Privacy and Cybersecurity in the Digital Age: Implications for the Sharia-Compliant Digital Economy - Febrian Maulana Putra; Syamsul Hilal; Hanif , Hanif (WANARGI : Jurnal Manajemen Dan Akuntansi, 2024)
This study reveals that Islamic law has a robust foundation to address privacy and cybersecurity issues in the digital age. The principles of the Quran and Hadith, reinforced by the maqasid al-shariah approach, provide a comprehensive ethical framework for protecting digital information. An analysis of Islamic legal sources shows that while the Quran and Hadith do not explicitly discuss modern technology, fundamental principles can be applied in the digital context. Contemporary fatwas from various fatwa councils in the Islamic world demonstrate a consensus that protecting digital privacy and security is a Sharia obligation. However, this research also identifies a gap between theory and practice, and a need for further ijtihad to address new technologies. An analysis of cybersecurity practices in Islamic institutions reveals a disconnect between Sharia principles and actual implementation. This study recommends enhancing collaboration between scholars and technology experts, developing practical guidelines for the application of Sharia in cybersecurity, increasing digital literacy among religious leaders, and integrating Sharia-based digital ethics into Islamic education. Additionally, there is a need to promote the development of global standards related to privacy and cybersecurity from an Islamic perspective, and further research on the application of Islamic concepts in security technology.